THE INFLUENCE OF PSYCHOLOGICAL CONTRACTS AND WORK CLIMATE ON EMPLOYEE DETERMINATION BEHAVIOR THROUGH JOB SATISFACTION AS INTERVENING VARIABLES AT EMPLOYEES OF PT.BANK MANDIRI RETAIL COLLECTION RECOVERY UNIT MEDAN - Tulus Andre Leonardo; Prihatin Lumbanraja; Vivi Gusrini Rahmadani Pohan (CV. Radja Publika, 2023)
This study aims to test and analyze whether the psychological contract affects the job satisfaction of employees of PT Bank Mandiri Unit Retail Collection Recovery Medan. Does the work climate affect employee job satisfaction. Does the psychological contract affect employee deviant behavior. Does the work climate affect employees' deviant behavior. Does job satisfaction affect employees' deviant behavior. Does the psychological contract affect employee deviant behavior through job satisfaction at. Does the work climate affect employees' deviant behavior through job satisfaction on. This study used a quantitative method involving 42 respondents. Data collection was carried out using questionnaires. The results showed that the psychological contract had a significant effect on employee satisfaction at PT Bank Mandiri Unit Retail Collection Recovery Medan. Work climate has a significant effect on employee job satisfaction at PT Bank Mandiri Unit Retail Collection Recovery Medan. The psychological contract has a significant effect on deviant behavior of PT Bank Mandiri Unit Retail Collection Recovery Medan employees. Work climate has a significant effect on deviant behavior of PT Bank Mandiri Unit Retail Collection Recovery Medan employees. Job satisfaction has a significant effect on deviant behavior of PT Bank Mandiri Unit Retail Collection Recovery Medan employees. Psychological contracts have a significant effect on employee deviant behavior through job satisfaction at PT Bank Mandiri Unit Retail Collection Recovery Medan.